Performance of BFRP and GFRP Hollow Circular Steel columns subjected to axial compression loads - J, Sahaya Jeeva Rethnam; K, Dr. Ganesan; S C, Dr. Vettivel (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Recent research has been focused on rehabilitation and strengthening of deteriorated steel structures and bridges using Fiber Reinforced Polymer (FRP) materials. This paper deals with the behavior of FRP confinement of hollow steel sections subjected to axial compression loads. The load carrying capacity and buckling failure patterns of hallow steel sections strengthened by different FRP were studied experimentally. Numbers of circular hallow steel sections of same diameter with different L/D ratio test specimens were fabricated. Three different L/D ratio test specimens were used as control specimens. The different number of layers in FRP such as basalt (BFRP) and glass (GFRP) fabrics in different orientations has been fabricated. The effects of strengthened elements were observed under axial compression load. The load vz slenderness ratio, stress strain relationship, the ultimate load vz orientation and number of ply wrapping by different FRP were deeply analyzed and are plotted, tabulated and discussed. Besides local and overall buckling modes, failure patterns and rupturing of fiber of strengthened and non strengthened specimens were also observed. It is concluded that BFRP fabric wrapped by double layers in the circumferential direction elements withstand more axial compressive load than other strengthened and non strengthened elements.